Seepage rate and uniformity of the stalk composite pipe for subsurface irrigation - Songmei Zai; Huanyu Wei; Xuemei Liu; Feng Wu; Linbao Liu; Danting Liu; Xin Li; Weiye Liu; Zaiyu Li (Irrigation and Drainage, 2025)
An orthogonal experiment with three factors and three levels was conducted to study the seepage rate and uniformity of stalk composite pipe (SCP) under subsurface SCP irrigation (SSI). Furthermore, to determine the best application mode for SSI, the pipeline length, irrigation volume and inner–outer diameter of the SCP were considered at a 0.4 m working pressure. The three levels corresponding to each factor were 20, 40 and 60 m; 30, 45 and 60 L m⁻¹; and 28–60, 40–80 and 50–100 mm, respectively. The results indicated that the seepage rate gradually decreased with increasing pipeline length. The pattern of the change in the seepage rate with irrigation volume was not obvious. There was a positive correlation between the seepage rate and the inner–outer diameter of the SCP. The irrigation uniformity coefficient, which was calculated based on the width of the surface wetting front, gradually decreased with increasing pipeline length. The impact patterns of irrigation volume and inner–outer diameter on irrigation uniformity were ambiguous. The seepage rate reached its maximum at the pipeline length, irrigation volume and inner–outer diameter, which were 20 m, 30 L m⁻¹ and 50–100 mm, respectively. There was the highest irrigation uniformity, with a pipeline length, irrigation volume and inner–outer diameter of the SCP of 20 m, 60 L m⁻¹ and 40–80 mm, respectively.